2018
DOI: 10.1186/s12894-018-0361-4
|View full text |Cite
|
Sign up to set email alerts
|

Cancer detection rate of prebiopsy MRI with subsequent systematic and targeted biopsy are superior to non-targeting systematic biopsy without MRI in biopsy naïve patients: a retrospective cohort study

Abstract: BackgroundTo determine whether prebiopsy multiparametric magnetic resonance imaging (mpMRI) with subsequent systematic plus targeted biopsies for suspicious lesions improve prostate cancer detection compared with standard non-targeting systematic biopsies without mpMRI in biopsy-naïve patients.MethodsPatients who underwent their first prostate biopsy due to suspicion of prostate cancer were analyzed retrospectively to compare the biopsy outcomes between patients who received prebiopsy mpMRI (215 patients) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 26 publications
2
14
0
1
Order By: Relevance
“…Our results are in line with previous studies that MRI followed by a targeted biopsy has a high negative predictive value for detection of clinically significant prostate cancers (26,27). In addition, the false negative rate was lower than 5%, which is in the same range as for mpMRI (6,28,29).…”
Section: Discussionmentioning
confidence: 54%
“…Our results are in line with previous studies that MRI followed by a targeted biopsy has a high negative predictive value for detection of clinically significant prostate cancers (26,27). In addition, the false negative rate was lower than 5%, which is in the same range as for mpMRI (6,28,29).…”
Section: Discussionmentioning
confidence: 54%
“…Traditionally, the decision about whether a prostate biopsy should be performed has been based mainly on PSA, digital rectal examination findings, and age, which leads to inaccurate results. 8 …”
Section: Discussionmentioning
confidence: 99%
“…Several studies report on the usefulness of mpMRI. 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 Porpiglia et al. 3 reported that a diagnostic pathway based on mpMRI had a higher detection rate than the standard approach for both PCa and clinically significant prostate cancer (csPCa).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent publications from the multicenter PROMIS and PRECISION trials have proven the value of mp‐MRI compared to targeted biopsy as an alternative to random biopsies in men with elevated PSA or abnormal DRE with increased significant cancer detection rates, less detection of insignificant cancers and in up to one‐third of men potentially obviating the need for biopsy altogether when mp‐MRI is negative. mp‐MRI before targeted biopsy in at‐risk men is rapidly becoming the standard of care in clinical practice …”
Section: Introductionmentioning
confidence: 99%